Laparoscopic partial splenectomy for splenic lymphangioma: a case report - Kotaro Kimura; Yo Kurashima; Kimitaka Tanaka; Yoshitsugu Nakanishi; Toshimichi Asano; Yuma Ebihara; Takehiro Noji; Soichi Murakami; Toru Nakamura; Takahiro Tsuchikawa; Keisuke Okamura; Toshiaki Shichinohe; et al. (Surgical Case Reports)
Abstract Background Lymphangioma is a benign malformation of the lymphatic system and is often found in the neck and axilla, the orbit, the mediastinum, etc. However, isolated splenic lymphangioma is a rare disease in young women, and its treatment is controversial. We report a case of laparoscopic partial splenectomy for isolated splenic lymphangioma in a young woman. Case presentation An 18-year-old woman with mild epigastralgia was admitted to a nearby hospital. Abdominal ultrasound detected a 6-cm mass confined to the upper pole of the spleen; thereafter, she was referred to our department for surgical treatment. Although a benign tumor, we decided to resect it because of her symptoms. To preserve part of the normal spleen, laparoscopic partial splenectomy was performed with a co-axial approach using four ports and a liver retractor in the lithotomy position. After dissection around the spleen hilum, we identified that the tumor was being fed from the splenic vessels of the upper pole and severed the branch. Postoperatively, the patient showed no complications and was discharged on postoperative day 8 without symptoms. Pathological examination revealed splenic lymphangioma, which is rare in young women. No recurrence was seen 1 year after surgery, and a computed tomography scan showed no problems with the remaining spleen. Conclusions In our experience of laparoscopic partial splenectomy for a young woman with an isolated splenic lymphangioma, we determined that laparoscopic partial splenectomy is a safe, effective, and valuable option for the treatment of benign splenic tumors.